ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI AUDIT DELAY PADA PERUSAHAAN SEKTOR KESEHATAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2018-2023 - ZUFRIZAL, ZUFRIZAL (LP2MTBM MAKARIOZ, 2024)
This study aims to analyze the factors that affect audit delays in health sector companies listed on the Indonesia Stock Exchange (IDX) during the 2018-2023 period. Audit delay is the time interval between the closing date of the company's books and the date of issuance of the audit report. This study uses multiple linear regression to test the influence of independent variables such as company size, profitability, leverage, operational complexity, and size of Public Accounting Firms (KAP) on audit delays. The results show that company size, operational complexity, and leverage have a significant influence on audit delay, while profitability and KAP size do not show a significant influence. These findings have important implications for company management and auditors in managing the audit process to be more efficient.